Evaluation of Clinical Symptoms and Laboratory Findings in Children with Coronavirus Disease 2019 - Okuyan, Ömer; Kızılyıldırım, Suna; Erkan Işık, Özlem; Barutçu, Adnan; Elgörmüş, Yusuf (Cerrahpaşa Medical Journal, 2023)
Objective: The incidence of coronavirus disease 2019 infection in children is increasing. We investigated the relationship between the distribution of coronavirus disease 2019 on age, gender, clinical, and laboratory findings in children. Methods: From March 2020 to March 2021, 192 pediatric patients with coronavirus disease 2019 (age: 0-18 years) were enrolled. Patients were divided into 5 groups as <1 age, 1-5 years, 6-10 years, 1-15 years, and 15-18 years. Coronavirus disease 2019 test were determined by the multiplex real-time polymerase chain reaction method. The demographic, clinical, laboratory, radiographic, and treatment data of the patients were obtained from the patients’ files. Results: Fever (44.79%), malaise (22.4%), and cough (19.27%) were the most common 3 symptoms seen in all coronavirus disease 2019 patients. Diarrhea (4.69%) and vomiting (4.17%) were the least common findings. C-reactive protein levels (19.63 ± 18.11 mg/L) were found to be above the normal limits, and procalcitonin values (0.03 ± 0.03 μg/L) were found within the normal limits in all of the patients. Family history was found in 96.35% of the patients, 51 (26.5%) were asymptomatic and 141 (73.5%) were symptomatic. Conclusion: Most of the pediatric coronavirus disease 2019 patients had mild symptoms, and the most common symptoms of the patients were fever and malaise. Although the parameters associated with poor prognosis are similar in general, it should be known that laboratory and imaging findings typical for adults and children may not accompany the disease and may present with different presentations. Cite this article as: Okuyan Ö, Kızılyıldırım S, Erkan Işık Ö, Barutçu A, Elgörmüş Y. Evaluation of clinical symptoms and laboratory findings in children with coronavirus disease 2019. Cerrahpaşa Med J. 2023;47(2):206-210.